Diabetes is associated with high risk of severe adverse events during chemotherapy for cancer patients: A single‐center study. Issue 3 (14th September 2022) - Mailliez, Aurélie; Ternynck, Camille; Duhamel, Alain; Mailliez, Audrey; Ploquin, Anne; Desauw, Christophe; Lemaitre, Madleen; Bertrand, Nicolas; Vambergue, Anne; Turpin, Anthony
Abstract: Diabetes mellitus (DM) is a common comorbidity among cancer patients, but its impact on chemotherapy tolerance has not been widely studied. We aimed to compare the occurrence of severe grade 3/4 adverse events (G3/4 AEs) within 90 days of starting chemotherapy between patients with and without diabetes. We conducted a retrospective single‐center study in Lille University Hospital Oncology Department, France. Patients who received the first cycle of chemotherapy for gastrointestinal, gynecological or cancer of unknown primary source between 1 May 2013 and 1 May 2016, were included. Overall, 609 patients were enrolled: 490 patients without diabetes (80.5%) and 119 patients with diabetes (19.5%). Within 90 days of starting chemotherapy, patients with diabetes had a significantly higher occurrence of AEs G3/4 compared to those with no diabetes (multivariate odds ratio [OR]: 1.57 [1.02‐2.42], P  = .04). More frequent G3/4 AEs in patients with diabetes were infection (26%), hematological disorders (13%), endocrine disorders (13%) and deterioration of the general condition (13%). In the year following the beginning of chemotherapy, patients with diabetes were twice as likely to be hospitalized as those without diabetes (univariate OR: 2.1 [1.40‐3.15], P  = .0003). After multivariate adjustment, diabetes was no longer significantly associated with the risk of hospitalization ( P  = .051). There were no differences between patients with and without diabetes regarding dose reduction and chemotherapy treatment delays ( P  = .61 and P  = .30, respectively). Our study suggests the need for better consideration of DM in the personalized care plan to improve chemotherapy tolerance and quality of life of patients with DM. Abstract : What's new? Diabetes mellitus is a frequent comorbidity in patients with cancer, but its impact on chemotherapy tolerance has not been widely studied. This retrospective study compared early chemotherapy tolerance within 90 days of starting the first chemotherapy cycle in patients with and without diabetes. The risk of severe adverse events after chemotherapy—including infection, hematological disorders, endocrine disorders and deterioration of the general condition—was significantly high in patients with diabetes. The study findings can guide the development of clinical strategies to improve chemotherapy tolerance and quality of life in patients with diabetes.